If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1 + -7x) + -11 = 5(-9x + 12) (1 * 7 + -7x * 7) + -11 = 5(-9x + 12) (7 + -49x) + -11 = 5(-9x + 12) Reorder the terms: 7 + -11 + -49x = 5(-9x + 12) Combine like terms: 7 + -11 = -4 -4 + -49x = 5(-9x + 12) Reorder the terms: -4 + -49x = 5(12 + -9x) -4 + -49x = (12 * 5 + -9x * 5) -4 + -49x = (60 + -45x) Solving -4 + -49x = 60 + -45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45x' to each side of the equation. -4 + -49x + 45x = 60 + -45x + 45x Combine like terms: -49x + 45x = -4x -4 + -4x = 60 + -45x + 45x Combine like terms: -45x + 45x = 0 -4 + -4x = 60 + 0 -4 + -4x = 60 Add '4' to each side of the equation. -4 + 4 + -4x = 60 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = 60 + 4 -4x = 60 + 4 Combine like terms: 60 + 4 = 64 -4x = 64 Divide each side by '-4'. x = -16 Simplifying x = -16
| 9(2x+5)=6 | | (u/5)-(9/20)=(u/4) | | 350=2w+2(3w-5) | | D(t-6)= | | u/5=(u/3)+4 | | x/-2-7=-3×-2 | | 6x+65=11x-4 | | x(x+0.6)=500 | | 0.25+1.5=n+1.5 | | x/2-7=-3×-2 | | X+(y+15)=55 | | 2x+3x-1=18 | | 9x(-5-6x)-1.3=0 | | 0=x^4-25 | | x*2-4x-5=0 | | 5x+x=232 | | 10-3x+8x=26 | | 11/10=r/11 | | 13=r/9x8 | | 330(0.5)^2/5.7 | | y+r+p=q | | -96+6=10x | | 1000mg=g | | 2x^2-12=18 | | y=2/3-5 | | r+y+p=q | | p+r+q=y | | 12=5-3/7w | | X+(x-2)+(x-8)=50 | | 10=7-3(4m-1) | | 10x-5y=11 | | 77=2x+9x |